The Effect of “Likes, Comments and Share” Feedback on Instagram on Self-Esteem of English Study Program - Zulfianti, Inayah; Sukmarini, Andi Vita; Djalil, Nur Alim (Borong Newinera Publisher, 2023)
This study aims to analyze the effect of Instagram usage, specifically likes, comments, and shares, on the self-esteem of students from the English Education Study Program (PBI) at Universitas Negeri Makassar (UNM), class of 2022. A total of 74 respondents were selected using purposive sampling, with the criteria of being active Instagram users. The data was collected through an online questionnaire and analyzed using t-test. The results from Instagram likes show a significance value of 0.000 (less than 0.05) and a t-count of 4.675 (greater than the t-table value of 1.99254), indicating that Instagram likes significantly affect students' self-esteem. The significance value of 0.002 (less than 0.05) and a t-count of 3.276 (greater than the t-table value of 1.99254) show that Instagram comments also significantly affect self-esteem. The significance value for Instagram shares is 0.002, with a t-count of 3.273, indicating that shares also significantly influence students' self-esteem. The conclusion of this study shows that interactions on Instagram, such as likes, comments, and shares, have a positive and significant impact on the self-esteem of PBI UNM class of 2022 students. This study supports the media ecology theory, suggesting that interactions on Instagram, such as likes, comments, and shares, help build self-identity and strengthen social connections, which ultimately leads to an increase in students' self-esteem.